A Classification Model and an Open e-Learning System Based on Intuitionistic Fuzzy Sets for Instructional Design Concepts. (September 2016) - Güyer, Tolga; Aydoğdu, Şeyhmus
This study suggests a classification model and an e-learning system based on this model for all instructional theories, approaches, models, strategies, methods, and technics being used in the process of instructional design that constitutes a direct or indirect resource for educational technology based on the theory of intuitionistic fuzzy sets (IFS). IFS is a set theory through expanding the membership systems of the classic theory of fuzzy sets in such a way to also involve the indeterminacies. As the model is grounded on a mathematical base, it also presents a convenient platform to define various metrics.